THE EFFECTS OF CORPORATE GOVERNANCE STRUCTURE AND FIRM CHARACTERISTIC TOWARDS ENVIRONMENTAL DISCLOSURE - Alfiandita Putri Fortunella; P. Basuki Hadiprajitno (Diponegoro Journal of Accounting, 2015)
This study aims to obtain empirical evidence about the effect of corporate governance structure and firm characteristic towards environmental disclosure of firms in Indonesia. Prior research review show that there is no consistency and have variety results. This research is a replication with modification of the research by Rao, et al (2012) and Burgwal and Vieira (2014) that examined the influence of corporate governance structure and firm characteristic on environmental disclosure. This study attempts to examine it with seven independent variables. These are independent commissioners, institutional ownership, board of commissioners size, proportion of women directors, firm size, profitability and industry type.The population of this study was all companies listed in Indonesia Stock Exchange (IDX) in 2012 and 2013. Sample consists of companies which disclose environmental disclosure through the GRI 3.1 index on sustainability report so there are 59 firms that determined as samples and 59 observations of financial statements. Analysis of Covariance (ANCOVA) test was used as an analysis technique to examine the hypotheses. Statistic program in this study used SPSS 20.The results of this study showed that independent commissioners, board of commissioners size and industry type have significant positive effect on environmental diclosure. While institutional ownership, proportion of women directors, firm size and profitability have no significant influence on environmental disclosure. This research showed that corporate governance practices and firm characteristic in Indonesia was still minimize to control the extent of environmental disclosure.